Experimental investigation on microstructure and mechanical properties of activated TIG welded reduced activation ferritic/martensitic steel joints. (January 2017) - Vora, Jay J.; Badheka, Vishvesh J.
Abstract: In the present study activated tungsten inert gas welding (A-TIG) process has been attempted for welding of 6 mm thick reduced activation ferritic/martensitic (RAFM) steel. Comparative studies on the effect of single (760 °C for 2 h) and double (760 °C for 2 h + 760 °C for 2 h) post-weld heat treatment (PWHT) cycles on microstructures, microhardness, tensile strength, impact strength and ductile to brittle transition temperatures (DBTT) of these welded joints have also been evaluated. It was inferred from the studies that ductility was improved for the weldments after undergoing double PWHT cycles. The toughness values increased after double PWHT cycles and were comparable to that of base metal values. DBTT values of −5 °C and −11 °C were obtained for the welded samples undergone single and double PWHT cycles respectively. This study also attested the detailed structure–property relationship of A-TIG weldments using optical microscopy, scanning electron microscopy, energy dispersive spectroscopy (EDS) techniques.